2015
DOI: 10.1007/s10044-015-0494-y
|View full text |Cite
|
Sign up to set email alerts
|

A biologically inspired framework for contour detection

Abstract: In this paper, we present a simple and efficient biologically inspired edge detection algorithm which attempts to model some structural features of the Human Visual System. More precisely, our edge detection approach attempts to model the dynamic retina concept, i.e., the natural saccadic eye movement process which redirects the fovea's attention from one point of interest to another within the image along with the inherent topological log-polar transformation (with its space-variant resolution) of the retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
(132 reference statements)
0
5
0
Order By: Relevance
“…This procedure changes image representation. 57 The result of Google aerial image segmentation would be a set of homogenous segments that cover the entire area. Each cluster contains a set of similar pixels that are similar in terms of certain characteristics, such as color, texture, or intensity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure changes image representation. 57 The result of Google aerial image segmentation would be a set of homogenous segments that cover the entire area. Each cluster contains a set of similar pixels that are similar in terms of certain characteristics, such as color, texture, or intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Image segmentation was originally developed to present an image using a set of categorized pixels and/or partition a digital image into multiple segments. This procedure changes image representation . The result of Google aerial image segmentation would be a set of homogenous segments that cover the entire area.…”
Section: Methodsmentioning
confidence: 99%
“…Contour, which is a curve joining all the continuous points along the boundary of the same color or intensity, is a useful tool for the spot detection and recognition [ 38 , 39 , 40 , 41 ]. In the findcontours function of the OpenCV library, we tried different finding modes and found that the “RETR-CCOMP” mode is the best choice.…”
Section: Methodsmentioning
confidence: 99%
“…Background segmentation was outside of the scope of this work; however, it is a necessary aspect of the system for correct deformation estimation. The development of generic target segmentation algorithms is a field of computer vision in and of itself, with several notable examples available in References [82][83][84][85].…”
Section: Background Segmentationmentioning
confidence: 99%